Alkene Metalates as Hydrogenation Catalysts - Büschelberger, Philipp (Chemistry, 2017)
First‐row transition‐metal complexes hold great potential as catalysts for hydrogenations and related reductive reactions. Homo‐ and heteroleptic arene/alkene metalates(1−) (M=Co, Fe) are a structurally distinct catalyst class with good activities in hydrogenations of alkenes and alkynes. The first syntheses of the heteroleptic cobaltates [K([18]crown‐6)][Co(η(4)‐cod)(η(2)‐styrene)(2)] (5) and [K([18]crown‐6)][Co(η(4)‐dct)(η(4)‐cod)] (6), and the homoleptic complex [K(thf)(2)][Co(η(4)‐dct)(2)] (7; dct=dibenzo[a,e]cyclooctatetraene, cod=1,5‐cyclooctadiene), are reported. For comparison, two cyclopentadienylferrates(1−) were synthesized according to literature procedures. The isolated and fully characterized monoanionic complexes were competent precatalysts in alkene hydrogenations under mild conditions (2 bar H(2), r.t., THF). Mechanistic studies by NMR spectroscopy, ESI mass spectrometry, and poisoning experiments documented the operation of a homogeneous mechanism, which was initiated by facile redox‐neutral π‐ligand exchange with the substrates followed by H(2) activation. The substrate scope of the investigated precatalysts was also extended to polar substrates (ketones and imines).